Factors Affecting the Formal Agriculture Credit Access in Kailali District, Nepal - Pandey, Prem; Timilsina, Ram Hari (Journal of Agriculture and Resource Management, 2024)
Nepal relies heavily on agriculture for economic growth. The availability of agricultural loans is crucial for promoting the growth and advancement of Nepal’s agricultural sector. Although the number of formal financial institutions is increasing in Nepal, access to credit among the majority of agricultural households remains limited. Getting credit from banks and other financial institutions was a challenging process. This study aimed to identify the factors affecting formal agriculture credit access among the farmers of the Kailali district of Nepal. Ward number one of Janaki Rural Municipality, Lamkichuwa, and Tikapur Municipalities of the Kailali district were purposively selected for the study. The primary data were collected through a household survey focus group discussion (FGD) and key informants interview (KII) whereas secondary data were obtained through a review of relevant literatures and publications like books, journals, articles. A random sampling technique was used to select 120 sample respondents, and a pre-tested semi-structured interview schedule was used to collect data from the respondent. Both descriptive and inferential statistics were used to analyze the data. Results of the logistic regression model revealed that cultivated land area, extension contact, membership of a farm-based organization, and training had a significant positive influence on farmers’ access to formal credit. Whereas, agriculture credit access was negatively and significantly influenced by the age of the household head.